DEVELOPMENT OF PUBLIC SERVICES IN KUANTAN SINGINGI DISTRICT - Desriadi; Afrinald Rizhan (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
Investment Service One Stop Integrated Service of Kuantan Singingi Regency in implementing public services as stipulated in Law Number 25 of 2009 concerning public services, which is an early indication of the problem. as stated in article 21 of Law Number 25 of 2009 concerning public services, namely Legal Basis, Requirements, Systems/mechanisms/procedures, Completion Periods, Costs/Tariffs, Service Products, Facilities and Infrastructure or Facilities, Executor Competency, Internal Supervision, Complaint Handling, Suggestions, and Feedback, Number of Executors, Guarantee of Service, Guarantee of Security and Convenience, and Performance Evaluation of Executors. So the purpose of this study specifically is to find out and explain public service standards from the aspects of requirements, systems/mechanisms/procedures, timeframe for completion, costs/tariffs, and executors' competence based on article 21 of Law Number 25 of 2009 concerning public services in the One-Stop Integrated Services Investment Service of Kuantan Singingi Regency as the organizer of public services.